2003
DOI: 10.1523/jneurosci.23-09-03735.2003
|View full text |Cite
|
Sign up to set email alerts
|

Netrin-1 Is a Chemorepellent for Oligodendrocyte Precursor Cells in the Embryonic Spinal Cord

Abstract: Netrin-1, secreted by floor plate cells, orients axon extension in relation to the ventral midline of the embryonic spinal cord. Oligodendrocyte precursor (OP) cells are born close to the ventral midline and migrate away from the floor plate. Here we show that OP cells, identified by expression of the platelet-derived growth factor alpha receptor, express the netrin receptors dcc and unc5h1 but do not express netrin-1. Using a microchemotaxis assay, we demonstrate that migrating OPs are repelled by a gradient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
84
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 125 publications
(92 citation statements)
references
References 63 publications
7
84
1
Order By: Relevance
“…The relative band densities of cells treated with PDGF and pharmacological inhibitors shows a clear increase in pERK following PDGF-A treatment, which is not blocked by the addition PD098059, but is markedly reduced in the presence of U0126. pERK levels are also markedly reduced in the presence of AACOCF 3 (Fig. 8c).…”
Section: Maintained Erk Phosphorylation From Transient Pdgf Exposurementioning
confidence: 77%
See 3 more Smart Citations
“…The relative band densities of cells treated with PDGF and pharmacological inhibitors shows a clear increase in pERK following PDGF-A treatment, which is not blocked by the addition PD098059, but is markedly reduced in the presence of U0126. pERK levels are also markedly reduced in the presence of AACOCF 3 (Fig. 8c).…”
Section: Maintained Erk Phosphorylation From Transient Pdgf Exposurementioning
confidence: 77%
“…8b, Lane 6). AACOCF 3 showed an apparent reduction in the level of pERK immediately after PDGF-A treatment (Fig. 8b, Lane 7) and at 24 h later (Fig.…”
Section: Maintained Erk Phosphorylation From Transient Pdgf Exposurementioning
confidence: 90%
See 2 more Smart Citations
“…To test whether the NO-induced cell migration and accumulation could be mediated by axon guidance/migration cues, we first analyzed the expression profile of Netrins in the GPs before and after SNP treatment ( Figure 1Bi-v) because Netrins were reported to be expressed in glial lineage cells [8,9]. The semi-quantitative RT-PCR and immunocytochemistry results indicated that both Netrin-1 and Netrin-4 were up-regulated in the GPs after SNP treatment (Figure 1Bi-v).…”
Section: Dear Editormentioning
confidence: 99%